Повторні хірургічні втручання за диференційованого раку щитоподібної залози - Гюльмамедов, С. І.; Сидоренко, Ю. О.; Сагалевич, А. І.; Чередниченко, С. І.; Вегнер, Д. В. (Clinical Endocrinology and Endocrine Surgery, 2009)
Taking into account recommendations of the "European consensus" on diagnostics and treatment of the differentiated thyroid carcinoma regularly there is a necessity in conducting of the repeated, radical surgical manuals at which probability of specific complications rises considerably. In work the results of the repeated surgical treatment are shown in 26 patients. Methods and ways of increase of radicalism and safety are analysed.